Venezuelan Aspect of “Emerging Partnership” between Turkey and Latin America: Factors, Dynamics and Risks - Andrei Nikolaevich Piatakov (Vestnik RUDN. International Relations, 2021)
The article provides an analysis of Turkish-Venezuelan relations amid Turkey-Latin American ties enhancing. In 2015-2019, this way of intercontinental cooperation has reached a peak. This was reflected in the intensification of trade and economic relations, as well as in the strengthening of diplomatic ties. The author analyzes the causes and international factors of the ongoing rapprochement. The analysis is carried out by tracking the trajectory of the changes in Turkey's foreign policy from the perspective of its gradual departure from the pro-Western course. The main emphasis is placed on the evolution and current stage of the Turkish-Venezuelan relations. After periods of recession and boom by 2016 relations between Venezuela and Turkey had come into a turning point. In recent years, their bilateral partnership has been markedly distinguished on the background of Ankaras relations with other states of the region. Venezuela has a record frequency of interstate official visits and a high degree of mutual understanding with the Turkish leadership on fundamental issues. The author carried out a comparative analysis of the two states political and historical special characteristics. The author comes to the conclusion that the format of Turkish-Venezuelan partnership is built on the basis of responding to common to the two states current external challenges. Both states are under sanctions pressure, although with a varying degrees of severity; both economies are experiencing crisis moments. These factors contribute to the development of economic interaction between the states on a mutually beneficial basis. For Venezuela, its economic cooperation with Turkey is a significant factor mitigating the negative effects of the permanent economic crisis. The supply of Turkish foodstuffs helps to reduce a food shortage, while Ankara's purchases of Venezuelan gold contribute to the replenishment of the Venezuelan budget with currency assets. We can talk about the existing geostrategic partnership, which has, if not long-term, then medium-term potential.